The Effectiveness of Structural Mitigation to Flood Disaster Reduction in Tebet, Matraman, and Jatinegara Sub-District of Jakarta City - Kesuma, Tri Nugraha Adi; Kusuma, Muhammad Syahril Badri; Farid, Mohammad; Kuntoro, Arno Adi; Rahayu, Harkunti Pertiwi (Universitas Ibn Khaldun, 2025)
Floods are the dominant color of the interaction of human activities and natural mechanisms that occur every year in the city of Jakarta. Various efforts have been made to reduce flooding in Jakarta, but flooding is still the dominant color, especially on the banks of the Ciliwung River. On the banks of the Ciliwung River, Tebet, Matraman and Jatinegara sub-districts are the three areas that experienced the most severe overflows of the Ciliwung River. Flood mitigation efforts in these three areas have been carried out in the form of increasing the drainage capacity of the Manggarai Gate and normalizing the river in the form of dredging and construction of embankments. However, this effort is not optimal because the implementation of normalization is hampered by social conflicts. This paper discusses mitigation efforts in the form of normalization and combination with retention ponds which are carried out by simulating flooded areas. Completion of the normalization of the Ciliwung River is not the best solution to deal with flooding in Jakarta. The flood volume which usually occupies the flood area flows quickly due to changes in the geometry of the river and causes changes in the hydrograph peak and causes flooding in the downstream part of the study area causing an increase in inundation area in Manggarai up to 200%. On the other hand, the use of retention/storage ponds on limited land has been able to reduce flood inundation by 10%. Therefore, staging in the planning and construction of flood mitigation infrastructure needs to be considered and planned thoroughly.